Investigation of the unified rain attenuation prediction method with data from tropical climates - Abdulrahman, A Y; Rahman, T A; Islam, Md Rafiqul; Olufeagba, B J; Abdulrahman, T A; Akanni, J; Amuda, S A Y (IEEE Journals, 2014)
The semi-empirical method recently proposed by Silva Mello and Pontes (SMP) for the prediction of rain attenuation in slant paths is investigated in this letter. The SMP method uses the simplified model of equivalent rain cell and the concept of an effective rain rate. However, substantial deviations were observed in SMP predictions when compared to the rain cell diameters derived from experimental data. The measured rain rates and attenuations were obtained from three tropical climates (Australia, and USM and IIUM both in Malaysia). The measured rain attenuation complementary cumulative distributions (CCDs) were also compared to SMP and the Rec. ITU-R P. 618-11. The test results show that the ITU-R model performs much better compared to SMP method in the three tropical climates.